Supply Chain Management Practices Of SME's In Malaysia - Zameni, Abdolhossein (2008)
The purpose of this research is to study of Supply Chain Management practices in Malaysia SME's. The objectives of supply chainmanagement (SCM) are described in logistic collaboration which is very important for the survival of companies in today competitive environment.